2014
DOI: 10.1371/journal.pone.0092117
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-Encapsulated ISMN: A Novel Nitric Oxide-Based Therapeutic Agent against Staphylococcus aureus Biofilms

Abstract: Background Staphylococcus aureus in its biofilm form has been associated with recalcitrant chronic rhinosinusitis with significant resistance to conventional therapies. This study aims to determine if liposomal-encapsulation of a precursor of the naturally occurring antimicrobial nitric oxide (NO) enhances its desired anti-biofilm effects against S. aureus, in the hope that improving its efficacy can provide an effective topical agent for future clinical use.Methodology S. aureus ATCC 25923 biofilms were grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…Among these signals, nitric oxide has been increasingly studied, especially because NO was shown to induce the dispersion of many pathogenic biolms (eg E. coli, Fusobacterium nucleatum, Staphylococcus aureus, and Vibrio cholerae) (Jardeleza et al 2014;Arora et al 2015;Barraud et al 2015), and to increase the sensitivity of bio lm bacteria to antibiotics (Barraud et al 2006;Barraud, Storey, et al 2009). However, bio lm formation by Azospirillum brazilense, Vibrio harveyi and Shewanella oneidensis appears to be induced by the addition of NO in the medium (Arruebarrena Di Palma et al 2013;Plate & Marletta 2012;Henares et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Among these signals, nitric oxide has been increasingly studied, especially because NO was shown to induce the dispersion of many pathogenic biolms (eg E. coli, Fusobacterium nucleatum, Staphylococcus aureus, and Vibrio cholerae) (Jardeleza et al 2014;Arora et al 2015;Barraud et al 2015), and to increase the sensitivity of bio lm bacteria to antibiotics (Barraud et al 2006;Barraud, Storey, et al 2009). However, bio lm formation by Azospirillum brazilense, Vibrio harveyi and Shewanella oneidensis appears to be induced by the addition of NO in the medium (Arruebarrena Di Palma et al 2013;Plate & Marletta 2012;Henares et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm forming strain S. aureus ATCC25923 was used in this study. Bacterial cultures were established as previously described (3). Briefly, bacterial strains (frozen glycerol stock) were inoculated onto nutrient agar (Oxoid) plates and incubated overnight at 37˚C for recovery.…”
Section: Construction Of the Pet28a-hla Recombinant Plasmid And Exprementioning
confidence: 99%
“…Chronic rhinosinusitis (CRS) is a common rhinology disease; the reported prevalence of Staphylococcus aureus (S. aureus) in CRS patients is 61% (1). Bacterial biofilms are considered as a common and important cause of persistent infections; biofilms require up to 1,000x higher antibiotic doses for effective treatment compared to planktonic cells, thus hindering eradication (2,3). Long-term use of antibiotics and emerging resistant bacteria pose a great threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the potential antibiofilm therapeutic effect of nasal NO in CRS, possibly as a result of the formation of toxic acidified nistabutrite derivatives . Jardeleza et al designed a liposomal formulation of a NO donor, isosorbide mononitrate, and demonstrated antibiofilm safety and efficacy in vitro and in a sheep model. The results were further supported by identification of taste receptors, such as T2R38, that detect molecules generated by Gram‐negative bacteria and activate NO production, found to be inversely correlated with the formation of biofilms in CRS patients, and discussed later …”
Section: Resultsmentioning
confidence: 99%